The Impact Of Artificial Intelligence Development On Personal Data Protection In An Effort To Achieve Legal Certainty - Sahat Maruli Tua Situmeang; Musa Darwin Pane; Diah Pudjiastuti (Faculty of Law, Universitas Pekalongan, 2025)
Artificial Intelligence (AI) has revolutionised various sectors, including law, by providing significant efficiency and innovation. However, this development also presents complex challenges related to data privacy. This research aims to analyse, first, how legal protection of personal data in AI applications can help achieve legal certainty, and second, what efforts are being made to strengthen the legal framework in addressing data privacy challenges posed by AI development. The legal research method used is normative legal research. The findings highlight that improvements are needed in the existing legal framework to be more responsive to AI advancements. Therefore, in order to achieve legal certainty, the legislature must develop more specific regulations regarding the use of AI in the context of personal data protection and establish a task force responsible for public outreach and education to raise public awareness about the importance of personal data protection